Second Birth Fertility in Germany: Social Class, Gender, and the Role of Economic Uncertainty - Michaela Kreyenfeld; Dirk Konietzka; Philippe Lambert; Vincent Jerald Ramos (European Journal of Population, 2023)
Building on a thick strand of the literature on the determinants of higher-order births, this study uses a gender and class perspective to analyse second birth progression rates in Germany. Using data from the German Socio-Economic Panel from 1990 to 2020, individuals are classified based on their occupation into: upper service, lower service, skilled manual/higher-grade routine nonmanual, and semi-/unskilled manual/lower-grade routine nonmanual classes. Results highlight the “economic advantage” of men and women in service classes who experience strongly elevated second birth rates. Finally, we demonstrate that upward career mobility post-first birth is associated with higher second birth rates, particularly among men.
Keywords: 300; Fertility; Germany; Uncertainty; Social class; Employment